Differences in microRNA-29 and Pro-fibrotic Gene Expression in Mouse and Human Hypertrophic Cardiomyopathy - Liu, Yamin; Afzal, Junaid; Vakrou, Styliani; Greenland, Gabriela V.; Talbot, C. Conover; Hebl, Virginia B.; Guan, Yufan; Karmali, Rehan; Tardiff, Jil C.; Leinwand, Leslie A.; Olgin, Jeffrey E.; Das, Samarjit; et al. (Frontiers in Cardiovascular Medicine, 2019)
Background: Hypertrophic cardiomyopathy (HCM) is characterized by myocyte hypertrophy and fibrosis. Studies in two mouse models (R92W-TnT/R403Q-MyHC) at early HCM stage revealed upregulation of endothelin (ET1) signaling in both mutants, but TGFβ signaling only in TnT mutants. Dysregulation of miR-29 expression has been implicated in cardiac fibrosis. But it is unknown whether expression of miR-29a/b/c and profibrotic genes is commonly regulated in mouse and human HCM. Methods: In order to understand mechanisms underlying fibrosis in HCM, and examine similarities/differences in expression of miR-29a/b/c and several profibrotic genes in mouse and human HCM, we performed parallel studies in rat cardiac myocyte/fibroblast cultures, examined gene expression in two mouse models of (non-obstructive) HCM (R92W-TnT, R403Q-MyHC)/controls at early (5 weeks) and established (24 weeks) disease stage, and analyzed publicly available mRNA/miRNA expression data from obstructive-HCM patients undergoing septal myectomy/controls (unused donor hearts). Results: Myocyte cultures: ET1 increased superoxide/H2O2, stimulated TGFβ expression/secretion, and suppressed miR-29a expression in myocytes. The effect of ET1 on miR-29 and TGFβ expression/secretion was antagonized by N-acetyl-cysteine, a reactive oxygen species scavenger. Fibroblast cultures: ET1 had no effect on pro-fibrotic gene expression in fibroblasts. TGFβ1/TGFβ2 suppressed miR-29a and increased collagen expression, which was abolished by miR-29a overexpression. Mouse and human HCM: Expression of miR-29a/b/c was lower, and TGFB1/collagen gene expression was higher in TnT mutant-LV at 5 and 24 weeks; no difference was observed in expression of these genes in MyHC mutant-LV and in human myectomy tissue. TGFB2 expression was higher in LV of both mutant mice and human myectomy tissue. ACE2, a negative regulator of the renin-angiotensin-aldosterone system, was the most upregulated transcript in human myectomy tissue. Pathway analysis predicted upregulation of the anti-hypertrophic/anti-fibrotic liver X receptor/retinoid X receptor (LXR/RXR) pathway only in human myectomy tissue. Conclusions: Our in vitro studies suggest that activation of ET1 signaling in cardiac myocytes increases reactive oxygen species and stimulates TGFβ secretion, which downregulates miR-29a and increases collagen in fibroblasts, thus contributing to fibrosis. Our gene expression studies in mouse and human HCM reveal allele-specific differences in miR-29 family/profibrotic gene expression in mouse HCM, and activation of anti-hypertrophic/anti-fibrotic genes and pathways in human HCM.